Positional profiling feasibility of U18 ice-hockey players based on anthropometry and aerobic capacity / Attila Czont, Zsolt Bodor, and Ildiko Miklossy - Czont, Attila; Bodor, Zsolt; Miklossy, Ildiko (2024)
Identification of talented players necessitates both subjective and objective evaluations of their playing ability and performance. Evaluating anthropometric characteristics and general physiological performance can aid sports professionals in player selection. This study aimed to determine if positional profiling is feasible for national-level ice hockey players by examining their anthropometric characteristics and physiological performance in two different seasons. The study included two U18 ice hockey teams from the “Székelyföldi” Ice Hockey Academy (SZJA). Data collection occurred in May 2020 and June 2023 at the SZJA’s Medical and Methodological Center. Body height, including barefoot height, was measured using a wall-mounted stadiometer (± 0.1 cm accuracy), while body weight was recorded with a standard scale. A standard incremental maximal oxygen uptake test was conducted in the laboratory using open-circuit spirometry and computerised instrumentation (CPET Cosmed, Italy) following the Bruce protocol. Additionally, cortisol levels were measured by ELISA from saliva samples to assess the players’ physical stress levels. Descriptive statistics revealed no significant differences in anthropometric characteristics between forwards and defensemen. However, some potential differences in maximal and absolute oxygen uptake rates were observed. Although descriptive statistics indicated no significant differences between the two positions, the Mann-Whitney U test, considering.